Physical-recreate activities to occupy the free time of handicaps children aged 6 to 11 - Lizmary Feriz Otaño; Yanelbys Miranda-Acosta; Raidelin Hernández Porraspita (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2013)
The research answers to the scholar age children's necessity of Hermanos Cruz Community in Pinar del Río municipality. To verify the existence of a real problem about the necessity to occupy the free time o handicaps children, an initial diagnosis was carried out using different methods of investigation such as theoretical, empirical, and statistical and community intervention methods. There were consulted some specialists so as to gather the necessary information to validate the proposal, that contributes to insert the children in society as a way of relaxing and also promoting them health. The participative techniques are aimed to transform the group's way of acting in the community. The proposed physical and recreate activities are integrating and take into account the children's psychobiological necessities. The proposal was greatly accepted by Hermanos Cruz community and its results were considerably higher than those ones expected in the investigation.